2021
DOI: 10.3390/cells10113021
|View full text |Cite
|
Sign up to set email alerts
|

Adult Neural Stem Cells from Midbrain Periventricular Regions Show Limited Neurogenic Potential after Transplantation into the Hippocampal Neurogenic Niche

Abstract: The regulation of adult neural stem or progenitor cell (aNSC) proliferation and differentiation as an interplay of cell-intrinsic and local environmental cues remains in part unclear, impeding their role in putative regenerative therapies. aNSCs with all major properties of NSCs in vitro have been identified in a variety of brain regions beyond the classic neurogenic niches, including the caudal periventricular regions (PVRs) of the midbrain, though active neurogenesis is either limited or merely absent in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 75 publications
(130 reference statements)
0
3
0
Order By: Relevance
“…GFAP was chosen to identify the multidirectional differentiation ability of NSCs 50 . As a principal constituent of the axonal cytoskeleton, β III Tuj1 is widely used as a marker to distinguish neurons from other cell types 51 . Thus, a positive staining indicated that the cultured cells were NSCs.…”
Section: Resultsmentioning
confidence: 99%
“…GFAP was chosen to identify the multidirectional differentiation ability of NSCs 50 . As a principal constituent of the axonal cytoskeleton, β III Tuj1 is widely used as a marker to distinguish neurons from other cell types 51 . Thus, a positive staining indicated that the cultured cells were NSCs.…”
Section: Resultsmentioning
confidence: 99%
“…Later, Zhao and colleagues revealed that adult NSCs transplantation improved locomotor function in spinal cord transection rats, which associated with nerve regeneration and IGF-1R expression [ 85 ]. Recently, Fauser and colleagues successfully transplanted adult NSCs from midbrain periventricular regions into the hippocampal neurogenic niche [ 86 ]. Lv and colleagues evaluated the safety and efficacy of adult NSCs transplantation for cerebral palsy [ 87 ].…”
Section: Adult Nscsmentioning
confidence: 99%
“…With the progressive ageing of the global population, neurodegenerative diseases have emerged as a prominent contributor to compromised quality of life and increased mortality rates among the elderly (Cacabelos, 2017; Chang et al, 2021; Fereshtehnejad et al, 2019). It is due to the limited regenerative capacity of the adult nervous system and the death or irreversible dysfunction of the neural cells (Achilleos & Trainor, 2012; Fauser et al, 2021; Matsubara et al, 2021). Currently, the drugs approved by the Food and Drug Administration (FDA) such as MDA receptor antagonists, levodopa, and donepezil are used to prolong neurodegeneration by supplementing neurotransmitters and neurotrophic factors (Gao et al, 2022; Honorio et al, 2022; Nagai et al, 2022; Osmaniye et al, 2023; Rants'o et al, 2022; Safarpour et al, 2022).…”
Section: Introductionmentioning
confidence: 99%